Screening of low oxalate content in M1V4 Mutant Line of TARO (Colocasia esculenta) CV. Wangi / Nur Alia Nadhirah Zainal ... [et al.] - Zainal, Nur Alia Nadhirah; Maadon, Siti Nursyazwani; Baharin, Siti Nor Atika; Hasan, Nor'Aishah (UiTM Cawangan Negeri Sembilan, 2022)
Raw taro causes unpleasant sensations such as prickliness or itchiness, hence it needs to be cooked before consumption. It is caused by calcium oxalate that formed as needle-shaped crystals in parts of taro, Colocasia esculenta. The purpose of this study is to determine the effects of chronic gamma irradiation in local taro cultivar, Wangi to its oxalate content. The effect of gamma irradiation in mutant line of taro, M1V4 to reduce the oxalate content was discussed. Using volumetric analysis, total oxalate content is significantly reduced in the treatment groups as compared to the control group. Treatment groups 1 (0.66 Gy) and 2 (0.33 Gy) that has been exposed to the highest dosages of chronic gamma irradiation reported the lowest oxalate contents among the samples. The results analyzed with one-way ANOVA and least significant difference (LSD) test supported that a higher dosage of gamma irradiation affected the oxalate content in the corms adversely. Although chronic gamma irradiation is found to be capable of reducing oxalate content in taro corms, precise and critical methods should be employed to evaluate for low oxalate content in taro mutant lines.